2021
DOI: 10.1017/s1049023x21000510
|View full text |Cite
|
Sign up to set email alerts
|

Association between Mode of Transportation and Survival in Adult Trauma Patients with Blunt Injuries: Matched Cohort Study between Police and Ground Ambulance Transport

Abstract: Introduction: Early police transport (PT) of penetrating trauma patients has the potential to improve survival rates for trauma patients. There are no well-established guidelines for the transport of blunt trauma patients by PT currently. Study Objective: This study examines the association between the survival rate of blunt trauma patients and the transport modality (police versus ground ambulance). Methods: A retrospective, matched cohort study was conducted using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Of these, 8 articles evaluated transport for penetrating trauma, 2 articles evaluated transport for blunt trauma, and 1 article evaluated both. No differences were found in mortality between EMS or police transport 20–24 . One study estimated that 64% of patients transported by police in Philadelphia may have benefited from prehospital interventions typically provided by EMS, such as intravenous fluids, spinal immobilization, or endotracheal intubation 25 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 8 articles evaluated transport for penetrating trauma, 2 articles evaluated transport for blunt trauma, and 1 article evaluated both. No differences were found in mortality between EMS or police transport 20–24 . One study estimated that 64% of patients transported by police in Philadelphia may have benefited from prehospital interventions typically provided by EMS, such as intravenous fluids, spinal immobilization, or endotracheal intubation 25 …”
Section: Resultsmentioning
confidence: 99%
“…Qualitative work involving Black trauma patients transported by police observed mixed responses 26,27 . Although some patients found police transport to be a positive experience, improving their transport times and serving as evidence of public service, others described it as “dehumanizing” and emotionally traumatic 23 . Other concerns included a lack of precautionary measures (eg, spinal precautions) and occupational hazard to police of transporting patients without appropriate training or equipment, including personal protective equipment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall survival rate of adult blunt trauma patients was found to be similar for police transported and EMS transported patients (99.2%; P = 1.000). 20…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Simultaneously, a growing body of literature has suggested that police transport is a safe and effective counterpart to traditional EMS-based transport. [7][8][9][10][11] Although an increasing number of cities across the United States have recognized the utility of police transport and implemented policies permitting it, Philadelphia remains the only major urban center to routinely use this practice. 6,8,12,13 Many studies have hypothesized that the benefit of police-based hospital transport lies in its efficiency.…”
mentioning
confidence: 99%